Antibody-Drug Conjugates in the Pipeline for Treatment of Melanoma: Target and Pharmacokinetic Considerations - Ina Lami; Andrew J. Wiemer (Adis, Springer Healthcare, 2024)
Abstract Melanoma is an aggressive, rapidly developing form of skin cancer that affects about 22 per 100,000 individuals. Treatment options for melanoma patients are limited and typically involve surgical excision of moles and chemotherapy. Survival has been improved in recent years through targeted small molecule inhibitors and antibody-based immunotherapies. However, the long-term side effects that arise from taking chemotherapies can negatively impact the lives of patients because they lack specificity and impact healthy cells along with the cancer cells. Antibody-drug conjugates are a promising new class of drugs for the treatment of melanoma. This review focuses on the development of antibody-drug conjugates for melanoma and discusses the existing clinical trials of antibody-drug conjugates and their use as a melanoma treatment. So far, the antibody-drug conjugates have struggled from efficacy problems, with modest effects at best, leading many to be discontinued for melanoma. At the same time, conjugates such as AMT-253, targeting melanoma cell adhesion molecule, and mecbotamab vedotin  targeting AXL receptor tyrosine kinase, are among the most exciting for melanoma treatment in the future.